The Desiring Eye : Photographs from Moderna Museet's Collection. - Elliott, David; Wigh, Leif (Stockholm : Moderna museet, 1998)
Abbott, Berenice ; Adams, Ansel ; Adamson, Robert ; Altobelli, Gioaccino ; Annan, Thomas ; Atget, Eugène ; Barnett, Walter ; Barraud, William ; Berggren, Guillaume ; Bonfils, Félix ; Brandt, Bill ; Braun, Adolphe ; Callahan, Harry ; Cameron, Julia Margaret ; Cartier-Bresson, Henri ; Cunningham, Imogen ; Curtis, Edward Sheriff ; Disdéri, André Adolphe Eugène ; Evans, Walker ; Fenton, Roger ; Fergus, John ; Frank, Robert ; Frith, Francis ; Fritz, Adolf ; Gibson, Ralph ; H.E.W. ; Hill, David Octavius ; Käsebier, Gertrude ; Knudstrup, Anna ; Kühn, Heinrich ; Langdon Coburn, Alvin ; Levitt, Helen ; Man Ray ; Mantz, Werner ; Micheler ; Morgan, Barbara ; Mulnier, Ferdinand ; Newman, Arnold ; Percheid, Nicola ; Renger-Patzsch, Albert ; Rude, Ernest ; Salomon, Adam ; Samuel, Antonio ; Sébah, J. Pascal ; Shaw, George Bernard ; Steichen, Edward ; Stieglitz, Alfred ; Strand, Paul ; Summons, Herbert Yowall ; Tournachon), Nadar (Gaspard Félix ; Watkins, Carleton Eugene ; Weston, Edward ; White, Clarence Hudson ; Zwart, Piet
biografie
The Desiring Eye : Photographs from Moderna Museet's Collection, August 29 - November 15, 1998
Engels & Zweeds
kunstcatalogus